KORELASI LINGKAR SKROTUM TERHADAP UKURAN TUBUH DAN BOBOT BADAN PADA KAMBING SABURAI: CORRELATION OF SCROTAL CIRCUMFERENCE TO MORPHOMETRICS AND BODY WEIGHT IN SABURAI GOATS - Arifin, Dani Nur; Wicaksana, Kunaifi; Widiarta, I Putu Gede Didik; Qamara, Cori; Adiputra, Kirana Dara Dinanti (Tropical Animal Science, 2025)
This study aims to identify the relationship between scrotal circumference (SC) to body weight (BW) and body size, namely body length (BL) and chest circumference (CC), as one of the predictors of male selection. This study was conducted on male Saburai goats at the Saburai Goat Breeding Center, Lampung. The approach used was quantitative observational with correlational and comparative study methods for each observed variable. The data obtained amounted to 24 goats starting from birth, three months, six months, nine months, and 12 months. The results showed a significant positive correlation (p <0.05) between SC and BW, BL, and CC, with the highest correlation shown between SC and BW (r = 0.72). This confirms that the size of the scrotal circumference can be an indicator of body weight, and body weight is the main indicator in determining testicular development as reproductive potential of males in Saburai goats.